Comparing the responses of bryophytes and short‐statured vascular plants to climate shifts and eutrophication. (28th November 2016) - Virtanen, Risto; Eskelinen, Anu; Harrison, Susan
Summary: Few experimental studies have tested how abundance and diversity of grassland bryophytes respond to global environmental changes such as climate shifts and eutrophication. Because bryophytes in grasslands are low‐statured, and because plant height is a key functional trait governing plant responses to resource gradients, their responses to these factors could resemble those of better‐studied small vascular plants. Alternatively, traits unique to bryophytes could lead to qualitatively different responses than those of small vascular plants. In a semi‐arid Californian grassland system, where bryophytes are at relatively low abundance and their ecology has been little studied, we compared changes in cover and species richness of bryophytes and short‐statured vascular plants in response to 5 years of experimental fertilization, springtime watering and fertilization + watering, which produced strong gradients in vascular plant biomass. Supporting our hypotheses, the cover and richness of both bryophytes and short vascular plants were negatively related to total community biomass and tall vascular plant cover, and declined in response to the fertilization + watering treatment, in which the cover of tall vascular plants most strongly increased. Two divergent responses were also observed as follows: watering alone increased the cover of bryophytes but not short vascular plants, while fertilization alone reduced the cover of short vascular plants but not bryophytes. Bryophytes and short‐statured vascular plants in grasslands both may be expected to decline under projected global changes in climate and nutrient deposition that enhance total community biomass and competitive pressure. However, shifts in either precipitation or eutrophication regimes alone may have differential effects on bryophytes and short vascular plants in grasslands, and organism‐specific plant functional traits must also be considered. A lay summary is available for this article. Abstract : Lay Summary